2021
DOI: 10.1038/s41575-020-00390-5
|View full text |Cite
|
Sign up to set email alerts
|

The International Scientific Association for Probiotics and Prebiotics (ISAPP) consensus statement on fermented foods

Abstract: An expert panel was convened in September 2019 by The International Scientific Association for Probiotics and Prebiotics (ISAPP) to develop a definition for fermented foods and to describe their role in the human diet. Although these foods have been consumed for thousands of years, they are receiving increased attention among biologists, nutritionists, technologists, clinicians and consumers. Despite this interest, inconsistencies related to the use of the term ‘fermented’ led the panel to define fermented foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
341
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(356 citation statements)
references
References 179 publications
1
341
0
14
Order By: Relevance
“…Fermented foods and beverages are defined as foods made through desired microbial growth and enzymatic conversions of food components (Marco et al, 2021). Yoghurt, Kefir, Miso, Natto, Tempeh and most Kombuchas are some of the available fermented foods that contain live microorganisms (Marco et al, 2021).…”
Section: Fermented Foods As a Possible Alternative To Probiotic Supplementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented foods and beverages are defined as foods made through desired microbial growth and enzymatic conversions of food components (Marco et al, 2021). Yoghurt, Kefir, Miso, Natto, Tempeh and most Kombuchas are some of the available fermented foods that contain live microorganisms (Marco et al, 2021).…”
Section: Fermented Foods As a Possible Alternative To Probiotic Supplementsmentioning
confidence: 99%
“…Fermented foods and beverages are defined as foods made through desired microbial growth and enzymatic conversions of food components (Marco et al, 2021). Yoghurt, Kefir, Miso, Natto, Tempeh and most Kombuchas are some of the available fermented foods that contain live microorganisms (Marco et al, 2021). Historically, many foods have undergone fermentation as a food preservation technique (Paul Ross et al, 2002;Dimidi et al, 2019) since the generation of antimicrobial metabolites like organic acids, ethanol and bacteriocins reduce the risk of contamination with pathogenic microorganisms (Dimidi et al, 2019).…”
Section: Fermented Foods As a Possible Alternative To Probiotic Supplementsmentioning
confidence: 99%
“…Prebiotics are non-digestible dietary components (e.g., oligosaccharides, fiber and inulin) that promote the proliferation of commensal gut microbiota with beneficial effects on health [26]. We could expect a beneficial effect on gut commensal microbiota in ICU patients with an improved resistance to colonization by detrimental bugs.…”
Section: Prebioticsmentioning
confidence: 99%
“…Another consensus statement of the International Scientific Association for Probiotics and Prebiotics reported the definition of fermented foods as "foods made through desired microbial growth and enzymatic conversions of food components" [11]. Although fermented foods have been consumed for thousands of years, they have been receiving increased attention among biologists, nutritionists, technologists, clinicians and consumers, as research has shown that fermented foods could improve gastrointestinal and systemic health [11][12][13][14][15]. Delivery of probiotics through fermentation [16] is a synergistic approach that uses the positive effects of both fermented foods and probiotics.…”
Section: Introductionmentioning
confidence: 99%